External acidity as performance descriptor in polyolefin cracking using zeolite-based materials - Rejman, Sebastian; Reverdy, Zoé M.; Bör, Zeynep; Louwen, Jaap N.; Rieg, Carolin; Dorresteijn, Joren M.; van der Waal, Jan-Kees; Vogt, Eelco T. C.; Vollmer, Ina; Weckhuysen, Bert M. (Nature communications, 2025)
Thermal pyrolysis is gaining industrial adoption to convert large volumes of plastic waste into hydrocarbon feedstock. However, it suffers from a high reaction temperature and relatively low selectivity. Utilizing a catalyst in the process, moving from thermal pyrolysis to catalytic cracking could help overcome both challenges. In order to develop efficient catalyst materials for this process, understanding structure-composition-performance relationships is critical. In this work, we show that in contrast to cracking of small molecules, plastic cracking activity using ultrastable zeolite Y materials does not depend on the bulk Brønsted acid site content, but rather on the concentration of acid sites located on the outer surface and in mesopores. This external acidity, however, fails to capture all the observed performance trends. Detailed kinetic experiments reveal that the scaling of the reaction rate with the catalyst loading differs drastically between highly similar catalyst materials. More specifically, doubling the catalyst loading leads to doubling of the reaction rate for one material, while for another it leads to more than fivefold increase. When very bulky reactants, such as polyolefins, are converted over microporous catalysts, structure-composition-performance relationships established for smaller molecules need to be revisited. Catalytic cracking is an emerging technology allowing to convert plastic waste into hydrocarbon feedstocks. Here, the authors show that the activity of ultrastable zeolite Y depends on the concentration of acid sites located outside of micropores.